2018
DOI: 10.1039/c8tb01215f
|View full text |Cite
|
Sign up to set email alerts
|

Rapid formulation of redox-responsive oligo-β-aminoester polyplexes with siRNAviajet printing

Abstract: Novel reduction responsive oligo-β-aminoesters were successfully synthesized and condensed with siRNA through an inkjet method, thus showing promising biological response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The silencing efficiency was evaluated after 1 h and 4 h of NP incubation into cancer cells and compared to untreated cells. As previously stated, we have already demonstrated the ability of free OBAEs to deliver siRNA in cancer cells, 27 but due to the cytotoxicity of this cationic material, we decided to not include this control in the following experiments. For redox responsive PLGA-SS-PEG NPs, approximately 50% of silencing efficiency occurred after only 1 h of incubation, with a slight increase over time.…”
Section: Effects Of Nps In Lung Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The silencing efficiency was evaluated after 1 h and 4 h of NP incubation into cancer cells and compared to untreated cells. As previously stated, we have already demonstrated the ability of free OBAEs to deliver siRNA in cancer cells, 27 but due to the cytotoxicity of this cationic material, we decided to not include this control in the following experiments. For redox responsive PLGA-SS-PEG NPs, approximately 50% of silencing efficiency occurred after only 1 h of incubation, with a slight increase over time.…”
Section: Effects Of Nps In Lung Cancer Cellsmentioning
confidence: 99%
“…26 For this study, we have employed a disulfide-containing OBAE, which, as we recently reported, was able to condense siRNA into polyplexes through a fast inkjet printing method. 27 The specific OBAE in this study was expected to protect siRNA against biological delivery barriers but also break down intracellularly to enable complete release of the nucleic acid cargo. 28,29 Through this chemical strategy, we combined the mucus penetration properties of PEG-coated NPs, 30 thus enhancing pulmonary delivery, with functionality for nucleic acid binding in the OBAE component, and bioresponsive chemistries in both components encoding for site-specific release.…”
Section: Introductionmentioning
confidence: 99%
“…[ 35 ] PBAEs have been recently used as bioinks for 3D bioprinting to create a high‐throughput drug screening platform. [ 39,40 ] While PBAEs have shown promise in a range of biomedical applications, they have yet to be explored as a resin for 3D printing in PμSL.…”
Section: Introductionmentioning
confidence: 99%
“…43C). 162,163 Acylation of the resulting diol (58) or diamine (60) with acryloyl 61 164,165 Fig. 42 Common methods for the synthesis of disulfide-containing molecules.…”
Section: Common Methods For the Preparation Of Disulfide-containing M...mentioning
confidence: 99%